STRES AKUT KARENA BISING SEBAGAI PENYEBAB TERJADINYA XEROSTOMIA - Wilda Hafny Lubis (Faculty of Dentistry, Universitas Indonesia, 2015)
In general annoyance of noise appears after many years of exposure. The speeds of disturbance depend on level of noise, impulsive component and duration of exposure, personal sensitivity that unknown characteristic. Noise belonging to acute stress needs short period to occur different from sorrow that takes long period. Stress will activate the regulator nerve and maintain intern environment to creates the homeostasis. Stress condition in long period will influence hormonal system, autonomic system until the exhaustion stadium and a few emotional expressive will be fixed for example dry mouth. Stress will also influence immune system so it is not effective to destroy the virus, microorganism and irregular cell that finally cause oral diseases.